Artificial Intelligence Empowers Solid-State Batteries for Material Screening and Performance Evaluation - Wang, Sheng; Liu, Jincheng; Song, Xiaopan; Xu, Huajian; Gu, Yang; Fan, Junyu; Sun, Bin; Yu, Linwei (Nano-Micro Letters, 2025)
Solid-state batteries are widely recognized as the next-generation energy storage devices with high specific energy, high safety, and high environmental adaptability. However, the research and development of solid-state batteries are resource-intensive and time-consuming due to their complex chemical environment, rendering performance prediction arduous and delaying large-scale industrialization. Artificial intelligence serves as an accelerator for solid-state battery development by enabling efficient material screening and performance prediction. This review will systematically examine how the latest progress in using machine learning (ML) algorithms can be used to mine extensive material databases and accelerate the discovery of high-performance cathode, anode, and electrolyte materials suitable for solid-state batteries. Furthermore, the use of ML technology to accurately estimate and predict key performance indicators in the solid-state battery management system will be discussed, among which are state of charge, state of health, remaining useful life, and battery capacity. Finally, we will summarize the main challenges encountered in the current research, such as data quality issues and poor code portability, and propose possible solutions and development paths. These will provide clear guidance for future research and technological reiteration. Highlights: 1 The latest advancements in the application of machine learning (ML) for the screening of solid-state battery materials are reviewed. 2 The achievements of various ML algorithms in predicting different performances of the battery management system are discussed. 3 Future challenges and perspectives of artificial intelligence in solid-state battery are discussed.